Software Lets Devices Negotiate to Share Digital Content. - Paulson, Linda Dailey (Computer (00189162), 2009)
The article discusses technology under development by Wireless Grids Corp. Utilizing a variety of technologies including HTML, Javascript, and the Flash multimedia platform from Adobe Systems Inc., the firm's "Innovaticus" software enables disparate computing devices to organize themselves into ad hoc networks whose participants can work together and access shared content. At the outset Wireless will focus on the youth market, although applications for business and government could emerge in the future.